Revival approach to increase MSMEs resilience during COVID-19: experience from Aceh, Indonesia - Syafruddin Chan; Kurnia Asni (Proceedings of AICS - Social Sciences, 2021)
This research aims to analyze the real impact of the COVID-19 pandemic for Micro Small Medium Enterprises (MSMEs) and what recovery strategies are needed to be implemented from the perspective of business owners to be able to recover and be resilient in these difficult times. Although the negative impact is still felt very large, there are still business opportunities that can be explored in helping MSMEs rise from their difficulties, one of which is by utilizing digital technology, in addition to taking advantage of various assistance offered by the government through the national economic recovery program during the pandemic Covid-19 to push the MSMEs sector out of this turbulent condition. This study uses a quantitative descriptive method. Information was collected using online questionnaires and interviews with MSMEs owners in Aceh Indonesia, especially MSMEs who are members of and assisted by the Business incubator of Syiah Kuala University, including those who have graduated from the coaching program from this institution. The questionnaire was distributed to 50 MSMEs using a non-probability sampling technique. The results revealed, many of the respondents felt the negative impact of the Covid-19 pandemic. The biggest impact felt was a decrease in the number of sales turnover. As a consequence, the various efforts made, including business streamlining, reducing the number of employees, decreasing production levels and rescheduling credit payments from banking institutions. At the same time, taking advantage of business in the digital sector due to the implementation of the lockdown, many UMKMs in Aceh have turned to digital marketing, starting from very simple levels such as entering e-commerce to more advanced levels such as using the value ladder and funneling strategy to drive more traffic into their landing pages.Keywords: Revival Approach, Micro Small Medium Enterprises (MSMEs), Business incubator of Syiah Kuala University, Covid-19 pandemic, the value ladder and funneling strategy, landing pages